Newly discovered population of Aedes japonicus japonicus (Diptera: Culicidae) in Upper Bavaria, Germany, and Salzburg, Austria, is closely related to the Austrian/Slovenian bush mosquito population. Issue 1 (December 2016) - Zielke, Dorothee; Walther, Doreen; Kampen, Helge
Abstract Background The German mosquito surveillance instrument 'Mueckenatlas' requests the general public to collect and submit mosquito specimens. Among these, increasing numbers of individuals of invasive species have been registered. Specimens of the Asian bush mosquitoAedes japonicus japonicus submitted from German Upper Bavaria, where this species had not previously been recorded, triggered regional monitoring in mid-2015. Methods The search forAe. j. japonicus breeding sites and developmental stages concentrated on cemeteries in the municipality of origin of the submitted specimens and, subsequently, in the whole region. A virtual grid consisting of 10 × 10 km2 cells in which up to three cemeteries were checked, was laid over the region. A cell was considered positive as soon asAe. j. japonicus larvae were detected, and regarded negative when no larvae could be found in any of the cemeteries inspected. All cells surrounding a positive cell were screened accordingly. A subset of collectedAedes j. japonicus specimens was subjected to microsatellite andnad 4 sequence analyses, and obtained data were compared to individuals from previously discovered European populations. Results Based on the grid cells, an area of approximately 900 km2 was populated byAe. j. japonicus in Upper Bavaria and neighbouring Austria. Genetic analyses of microsatellites andnad 4 gene sequences generated one genotype out of two previously described for Europe and three haplotypes, one of which had previously been found in Europe only inAe. j. japonicus samples from a population in East Austria and Slovenia. The genetic analysis suggests the new population is closely related to the Austrian/Slovenian population. Conclusion AsAe. j. japonicus is well adapted to temperate climates, it has a strong tendency to expand and to colonise new territories in Central Europe, which is facilitated by human-mediated, passive transportation. The new population in Upper Bavaria/Austria is the seventh separate population described in Europe. According to our data, it originated from a previously detected population in eastern Austria/Slovenia and not from an introduction event from abroad. The dispersal and population dynamics ofAe. j. japonicus should be thoroughly surveyed, as this species is a potential vector of disease agents.